Postenucleation socket syndrome: surgical repair - Ramalho, M (2013)
Introduction: A contracted eye socket is a functional and cosmetic misfortune to the patient. It makes impossible to the patient to wear an eye prosthesis, but also becomes a source of chronic infection, discharge and irritation. There are several surgical techniques to deal with the postenucleation socket syndrome. Methods: Six consecutive patients with postenucleation socket syndrome underwent reconstruction of the anophthalmic socket. The cause for enucleation in 5 cases was related to trauma and a retinoblastoma in 1 case, all the cases presented to us several years after the enucleation and all the patients had difficulty or impossibility to wear the prosthesis. Results: All patients underwent surgery, which entailed scar tissue release, oral mucous membrane grafting and socket reconstruction. All patients who had surgery experienced significant improvement of socket contracture that enabled patients to wear a prosthesis again, improving significantly the quality of life. Conclusions: Surgical repair of the contracted socket using oral mucous membrane grafting can allow resumption of prosthesis wear. We describe 6 patients in which functional as well as aesthetic outcome was obtained.